PENERAPAN PEMBELAJARAN BERDIFERENSIASI MELALUI MODEL KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) DALAM PEMBELAJARAN PAI - Saniyah, Alfiyanah Wahyu (FIKRAH, 2025)
This study aims to analyze the implementation of the Independent Curriculum through the Teams Games Tournament (TGT) cooperative learning model in Islamic Religious Education (PAI) learning in class VIII of UPT SMP Negeri 3 Gresik. The Kurikulum Merdeka encourages more flexible, inclusive, and student-based learning, while the TGT model facilitates collaboration, active interaction, and healthy competition between students to improve their understanding and involvement. This study uses a qualitative approach with a descriptive research type. The results of the study indicate that the implementation of the TGT model can increase students’ active participation in PAI learning. Students who previously tended to be passive became more involved in group discussions and more confident in expressing their opinions. In addition, students’ understanding of PAI material also increased, especially in connecting religious values with their personal experiences.